Biorefining of seed oil cakes as industrial co-streams for production of innovative bioplastics. A review. (March 2021) - Mirpoor, Seyedeh Fatemeh; Giosafatto, C. Valeria L.; Porta, Raffaele
Abstract: Background: Numerous different seeds are utilized for edible oil extraction and seed by-products following oil extraction, known as seed oil cakes, represent roughly 50% of the original seed weight. Since seed oil cakes are rich in fibers, proteins and secondary metabolites, they are considered as promising candidates to be raw material to be consumed in a biorefinery for the production of high-value added products according to circular economy paradigms. Several studies have been performed on the potential uses of seed oil cakes derived from different plant species. Scope and approach: This review, resulting from a collection of experimental results by databases, as well as by topic and keyword search, summarizes the current use of most seed oil cakes so far utilized, as well as that of additional four seed cakes obtained from plants having an economically significant relevance due to their food, nutraceutical or pharmaceutical properties: sesame ( Sesamum indicum L.), hemp ( Cannabis sativa ), cardoon ( Cynara cardunculus ) and black cumin ( Nigella sativa ). Various attempts have been done to convert their protein content into a renewable source for producing biodegradable and edible plastics, potentially attractive mainly for food and agricultural industries, as substitutes of the highly polluting petroleum-based plastics. Key findings and conclusions: Seed oil cakes are generally used as animal feed supplementation, plant fertilizer or soil compost due to their high protein, carbohydrate and nitrogen contents. More recently, novel exploitations of the seed oil cakes are under study, such as the production of biofuels and bioplastics. Therefore, seed oil cakes may represent an attractive feedstock for the development of biorefineries through the edible or not edible oil production. Highlights: Most seed oil cakes (SOCs) are currently used as animal feed or plant fertilizers. SOCs represent an attractive feedstock for the development of new biorefineries. SOCs are an opportunity to generate protein added-value products. Proteins from SOCs may be turned into renewable sources for producing bioplastics. The current and the potential use as bioplastics feedstock of nine SOCs are reviewed.